Ortaöğretim 9 ve 12. sınıf öğrencilerinin sürdürülebilir çevre bilinci düzeyleri - İpek DERMAN; Nuray SENEMOĞLU (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study aims to investigate the level of sustainable environmental awareness (SEA) of 9th and 12th grade students and the ideas of students with regard to environment where they attained SEA behaviors. For this purpose, a SEA Scale was developed and implemented to 782 students. The scale comprised of 10 scenarios with three multiple choice options about them (Cronbach α=0.87). The result of this descriptive study shows that there was a significant difference between 9th graders and 12th graders in terms of SEA level (in favor of the 9th graders). In contrast, there was no significant difference between 9th and 12th graders in terms of achievement. In addition to this, all students stated that they acquired SEA behaviors mostly from TV, biology courses, family and the internet